1977
DOI: 10.1002/1097-0142(197706)39:6<2597::aid-cncr2820390644>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Lobular carcinomain Situ of the breast:An approach to rational treatment

Abstract: A review of 3299 benign breast lesions was carried out. Lobular carcinoma in situ (LCIs) was discovered in 52 cases; and of these, 44 had been treated by biopsy alone. During the follow-up period averaging 15.9 years, 11 patients developed invasive breast cancer (IBC): 9 ipsilateral lesions, and 4 contralateral. This was about 12 times the frequency expected. The development of IBC had no relation to the patient's age, nor could any correlation be drawn between the time periods which elapsed from the time of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
4

Year Published

1979
1979
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(52 citation statements)
references
References 16 publications
3
45
0
4
Order By: Relevance
“…1,18 They occur predominantly in premenopausal women, with most cases being diagnosed in women between 40 and 50 years of age. 13,[19][20][21][22] They are clinically occult, and although they are often also mammographically silent, a significant minority of lobular neoplasia cases diagnosed on core biopsy have associated microcalcifications. [23][24][25][26] Data derived from the Surveillance, Epidemiology and End Results Program 27 have shown that the ageadjusted, age-specific rates of LCIS among women in the United States has increased fourfold between the late 70s (0.9 per 100 000 person years) and late 90s (3.2 per 100 000 person years).…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…1,18 They occur predominantly in premenopausal women, with most cases being diagnosed in women between 40 and 50 years of age. 13,[19][20][21][22] They are clinically occult, and although they are often also mammographically silent, a significant minority of lobular neoplasia cases diagnosed on core biopsy have associated microcalcifications. [23][24][25][26] Data derived from the Surveillance, Epidemiology and End Results Program 27 have shown that the ageadjusted, age-specific rates of LCIS among women in the United States has increased fourfold between the late 70s (0.9 per 100 000 person years) and late 90s (3.2 per 100 000 person years).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…11,29,30 LCIS confers B15% absolute risk of developing breast cancer at 15 years, but a significant number of subsequent carcinomas occur more than 15 years after a diagnosis of LCIS. 2,12,[19][20][21] Although lobular neoplasia has been linked to an increased risk of subsequent carcinoma in either breast, 12,13,21 several studies have shown a higher, although not always statistically significant, risk in the ipsilateral breast. 3,14,17,20,30,31 Cancer risk in ALH seems to vary with patient age; an initial diagnosis of ALH in postmenopausal women has been associated with a lower risk of subsequent carcinoma development than in premenopausal women.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…to confirm the diagnosis of ADH, ALH, LCIS, DCIS, or invasive malignancy using the criteria established by Page and Anderson. 18,21,27 Each excision sample was classified, based on the histologic findings in the most significant lesion, as malignant (DCIS and/or IBC) or not malignant (ADH, ALH, LCIS, or other benign findings). Whenever a discrepancy existed between the histologic features of the core biopsy sample and the histologic features of the excision biopsy sample, the slides in question were re-reviewed by a study pathologist (D.C.A.)…”
Section: Histologic Reviewmentioning
confidence: 99%
“…Although the standard teaching has been that the development of a subsequent cancer can be in either breast, 29,30 some series report a higher risk of ipsilateral cancer compared with a contralateral cancer, and a greater than expected risk of developing invasive lobular carcinoma compared with invasive ductal carcinoma. 31,32 This might suggest that LN is more of a precursor lesion than previously suspected, but specific treatment of LN as a precursor lesion, as is done with DCIS, is not recommended.…”
Section: Management Of Ln As the Most Worrisomementioning
confidence: 99%